Cognitive Correlates of Counsellor Trainees’ Needs Awareness - Weikel, William J.; Loesch, Larry C. (Canadian Journal of Counselling and Psychotherapy, 2012)
This study examined the relationships between the differences in counsellor trainees' perceived and measured needs levels and their Graduate Record Examination (GRE) scores and grade point averages (GPA). Using definitions from the Personality Research Form (PRF), the counsellor trainees' predicted their needs levels in percentiles. They then completed the PRF following standard procedures. Differences between their perceived and measured needs levels were correlated with their GRE scores and undergraduate and graduate GPAs. GRE scores were generally inversely related to differences in measured and perceived needs levels; higher GRE scores were associated with smaller differences. GPAs were generally not significantly related to prediction accuracy.